7 - Thinking Political Emancipation and the Social Sciences in Africa: Some Critical Reflections - Neocosmos, Michael (Africa Development, 2021)
The freedom which Africa was to attain with liberation from colonialism had originally promised to emancipate all the people of the continent from poverty and oppression. Yet anyone can observe that this has not happened. Uhuru is still elusive; freedom seems unattainable. Nationalist, socialist and neo-liberal conceptions of human emancipation have all failed to provide a minimum of freedom for the majority of Africans who are living under conditions which worsen daily as the crisis of capitalism and liberal democracy worsens. All three of these views of freedom were elaborated and theorised as universal by the social sciences. It is these conceptions which still orientate our thought. The fact that freedom has not been achieved evidently means that our thinking has so far been deficient. This article argues that the social sciences have played their part in our inability to think freedom and are consequently in need of fundamental restructuring. Central to their limitations if not their failure to comprehend emancipation in a manner adequate to the problems of the twenty-first century in Africa, has arguably been their inability to take what excluded people say seriously enough. In the past they have been plagued by the notion that only those with knowledge and power are capable of thinking a new way forward, thus aligning their thinking with that of the state (either in its current or forthcoming form). Given the lack of success of the social sciences in thinking human emancipation so far, we should consider alternatives which are open to popular perspectives. The article argues for an expansion of the social sciences to include the idea that ‘people think’ in Africa, and that therefore reason is not exclusively the prerogative of academics and politicians. Marx once observed that ‘the state has need ... of a very stern education by the people’. This remark is even truer today than it was in his time.